Organization of knowledge control in practical classes on coordination chemistry - Столяренко, В. Г. (Pedagogy of Higher and Secondary Education, 2021)
Harmonization intellectual and emotional teaching constituents on every his stage is the guarantee of receipt the students of fundamental of hifh-quality education. Introduction of intellectual-emotional approaches in an educational process is illustrated on the example of organization of control of knowledges on practical trainings of cooedination chemistry.